IUCrJ on passing its tenth anniversary and entering its second decade: progress, current status and prospects for the future - Andrew. J. Allen (IUCrJ)
This Editorial briefly celebrates the history and progress of IUCrJ in its first decade, reviews its present status, and suggests some pointers for the future.